Influence of temperature during interfacial polymerization on the synthesis and separation performance of thin-film composite polyamide membranes - Leong, Yi Ning (Nanyang Technological University, 2023)
Thin-film composite (TFC) membranes are widely used across all modes of osmosis. The overall performance of the membrane is highly dependent on the polyamide (PA) active layer that is responsible for its selectivity. A change in PA layer morphology would affect the separation properties of the membrane. In this paper, the PA synthesis parameters were chosen after a careful review of the effect of various reaction conditions. The effect of temperature on the interfacial polymerisation process was also investigated by using trimesoyl chloride (TMC) solutions of different temperatures. The resulting morphology and separation properties were studied by using scan electron microscopy (SEM) and reverse osmosis (RO) testing respectively. A change in the temperature of the organic solution was found to have the greatest impact on meta-phenylene diamine (MPD) diffusivity. Meanwhile, the instantaneous mixing of monomers has shown to be the domineering factor in determining the morphology of a PA layer.